Sharing, group-buying, social supply, offline and online dealers: how users in a sample from six European countries procure New Psychoactive Substances (NPS) - Werse, B.; Benschop, A.; Kamphausen, G.; van Hout, M.-C.; Henriques, S.; Silva, J.; Dabrowska, K.; Wieczorek, L.; Bujalski, M.; Felvinczi, K.; Korf, D. (International Journal of Mental Health and Addiction, 2019)
Given the multiple ways of regulations and market situations for new psychoactive substances (NPS), it is of interest how NPS users procure their drugs in different countries as well as in different user groups. Data comes from a face-to-face and online survey conducted in six EU countries, covering three groups of current (12-month) adult NPS users: (1) socially marginalized, (2) users in night life, and (3) users in online communities. While the supply situation differed considerably between countries, friends were the most prevalent source for buying, followed by online shops and private dealers. Marginalized users were more likely to buy from dealers, while online respondents showed the highest rates for buying online. While buying NPS from online or offline shops was relatively prevalent, we also found high rates for social supply and buying from dealers. A considerable part of this market may be classified as “social online supply,” with private suppliers procuring their drugs online. The market features among marginalized users resemble more those of illicit drug markets than those for other NPS users.